Fat-soluble Vitamins and Lung Cancer: Where We Are? - Lin, Xue; Wang, Yaxuan; Zhang, Tongzuo; Pu, Xiaoyan (Recent Patents on Anti-Cancer Drug Discovery, 2025)
Fat-soluble vitamins (vitamins A, D, E, and K) are vital substances for maintaining normal physiological functions in the body. In recent years, scholars have explored the relationship between fat-soluble vitamins and the wasting disease - lung cancer. In this paper, we review recent studies on fat-soluble vitamins and lung cancer to clarify the relevance and molecular mechanisms of various vitamins in lung cancer, and whether the levels of fat-soluble vitamins in the body and vitamin supplementation affect the development of lung cancer. Our review could facilitate the discovery of biomarkers, potential therapeutic targets in lung cancer, and anti-tumor adjuvant drugs, in addition to highlighting other new ideas in the prevention and treatment of lung cancer.
Keywords: Vitamins E